2012
DOI: 10.1590/s1516-35982012000800001
|View full text |Cite
|
Sign up to set email alerts
|

Apparent nutrient digestibility and mineral availability of protein-rich ingredients in extruded diets for Nile tilapia

Abstract: -Apparent digestibility coefficients (ADC) of gross energy and dry matter (DM) and mineral availability were evaluated for eight protein-rich ingredients (corn gluten meal, soybean meal, cottonseed meal at 280.0 and 380.0 g/kg, poultry by-product meal, meat meal, fish meal and feather meal) in compound diets for Nile tilapia. .582), and the lowest calcium and phosphorus availability were recorded for cottonseed meal at 280.0 g/kg. Therefore, poultry by-product meal appears to be the best ingredient for using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 32 publications
(37 reference statements)
2
13
1
5
Order By: Relevance
“…This correlation has been reported in other studies (Guimarães et al, 2012;Vidal et al, 2015). The GE digestibility observed in this study was similar to values reported for silver perch (77%) (Allan et al, 2000) but lower than values reported for hybrid tilapia, O. niloticus × O. aureus (81.5%) (Zhou & Yue, 2012).…”
Section: Digestibilitysupporting
confidence: 91%
See 1 more Smart Citation
“…This correlation has been reported in other studies (Guimarães et al, 2012;Vidal et al, 2015). The GE digestibility observed in this study was similar to values reported for silver perch (77%) (Allan et al, 2000) but lower than values reported for hybrid tilapia, O. niloticus × O. aureus (81.5%) (Zhou & Yue, 2012).…”
Section: Digestibilitysupporting
confidence: 91%
“…Dietary fiber is not entirely digested by most fish species (NRC 2011) and studies have reported that the dietary fiber content and ADCDM are related (Allan et al, 2000;Guimarães et al, 2012). The ADCDM value determined in this study is similar to values reported for the other fish species, such as silver perch, Bidyanus bidyanus (74.2%) (Allan et al, 2000); yellowfin seabream, Sparus latus (70.6%) (Wu et al, 2006); and hybrid tilapia, O. niloticus × O. aureus (66.6%) (Zhou & Yue, 2012).…”
Section: Digestibilitymentioning
confidence: 99%
“…Thus, four digestible protein levels (28.0, 35.0, 42.0, and 49.0% DP) at two digestible energy levels (3,200 and 3,600 kcal/kg) were tested comprising eight diets. Digestible protein and energy content of feedstuffs were calculated based on apparent digestibility coefficients reported for tilapia (PEZZATO et al, 2002;GUIMARÃES et al, 2008GUIMARÃES et al, , 2012.…”
Section: Experimental Diet and Diet Preparationmentioning
confidence: 99%
“…Aspecto semelhante foi observado por GONÇALVES et al(2005) quando avaliaram a disponibilidade do cálcio no farelo de soja, soja extrusada, farelo de algodão, glúten de milho e farelo de girassol, assim como por GUIMARÃES et al (2012) com o farelo de soja e o farelo de algodão. Entretanto, esses resultados diferem daqueles apresentados por KOPRUCU e OZDEMIR (2005), que obtiveram 20,3% para o glúten de milho e 29,0% para farelo de soja, e também por FURUYA et al (2001), que registraram coeficiente de disponibilidade igual a 85,04% para esse mineral no farelo de soja.…”
Section: Justificaram Os Valores Deunclassified
“…Os coeficientes de disponibilidade do magnésio obtidos no presente estudo são similares ao valor encontrado por GONÇALVES et al (2005) para o magnésio do glúten de milho (38,91%), mas se mostram relativamente inferiores àqueles obtidos por GUIMARÃES et al (2012) e GONÇALVES et al (2005, respectivamente, 72,62% e 75,61%. Para este mineral no farelo de algodão, os valores foram semelhantes ao apresentado por GONÇALVES et al (2005): 73,43%; contudo, os coeficientes obtidos na presente pesquisa mostraram-se superiores aos determinados neste ingrediente (37,49%) por GUIMARÃES et al (2012).…”
Section: Justificaram Os Valores Deunclassified